Monetary Targeting - Borivoje D. Krušković; Tina Maričić (Journal of Central Banking Theory and Practice, 2015)
In this paper we test the existence of long-term relationship between money supply and inflation, money supply and GDP and money supply and unemployment. Three independent panel cointegration regressions are evaluated where money supply is the explanatory variable, while inflation, GDP and unemployment rates occur as dependent variables. The sample consists of 17 countries (Australia, Canada, Chile, Denmark, Israel, Japan, South Korea, Mexico, New Zealand, Poland, Switzerland, United Kingdom and United States). The data are annual and refer to the period from 1990 to 2013. The results of the empirical analysis in this paper show that there is no significant long-term relationship between inflation and money supply, while there is statistically significant long-term relationship between GDP and money supply, as well as between unemployment rates and the money supply.
Keywords: E31; E41; E52; C33; 330; monetary targeting; inflation; money supply